PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM MENUNJANG PENINGKATAN PENGENDALIAN BIAYA PROYEK PADA PT. BUKIT JAYA ABADI - Aliya, Siti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The cost accounting information system is the whole procedure and technique are needed in order to collect theentire data of expenditure and process the data into information which is needed by the manager in monitoringthe work performance. The internal control structure in the cost accounting information system is an affectiveproject which becomes one of the important factors which is necessary to be applied to maximize the companyâsprofit. Some important aspects which are necessary to be considered are the purchasing system, and the paymentof salary and wages system. A better internal control approach can be achieved through comprehension of theexisting system by assessing its strengths and weaknesses. The result of research indicates that there are someshortages which have to be improvedin the company information system in order to be optimum in supportingthe cost control process, such as the separation of authority and responsibility of each department in thepurchasing process. In this purchasing process, the procurement department as the performer should have goodcontrol system. One of the recommendation solutions as the result of this research is to perform the separation oftask and function in written and documented in regard to every department that is using this informationsystem. By the existing improvement in the implementation of cost control therefore obstacles and cheats whichare occurred in the company can be minimized so an optimum profit can be achieved.Keywords: Accounting Information System, Cost Control, Internal Control.